Application of wood structures of linean electrical chains at standing input impacts - Simeonova, Tsvetelina (Yearbook Telecommunications, 2018)
The aim of the study is to develop a methodology using tree structures when analyzing a linear electrical circuit with a single source. The relationship between parameters of elements and parameters of equivalent elements and their corresponding electrical magnitude is used, current and voltage, with a specified source influence by analysis of the electric circuit with a tree description of the equivalent transformations. The following results were obtained: - Equivalent tree structure of the electrical circuit for determining the equivalent resistance (in the rights direction), and for determining the magnitudes (in the opposite direction). - An algorithm for determining equivalent resistance, as well as an algorithm for determining the magnitudes based on equivalent transformations. The work contributes with: A methodology for analyzing a linear electrical circuit with a single source based on a tree structure is proposed. Training of students in the area of theoretical electrical engineering to use analysis of DC circuit according to a proposed algorithm for application of tree structures, including an equivalent tree scheme and demo calculations is suggested.